list.v 147 KB
Newer Older
Robbert Krebbers's avatar
Robbert Krebbers committed
1
(* Copyright (c) 2012-2015, Robbert Krebbers. *)
2 3 4
(* This file is distributed under the terms of the BSD license. *)
(** This file collects general purpose definitions and theorems on lists that
are not in the Coq standard library. *)
5
Require Export Permutation.
6
Require Export numbers base decidable option.
Robbert Krebbers's avatar
Robbert Krebbers committed
7

8
Arguments length {_} _.
Robbert Krebbers's avatar
Robbert Krebbers committed
9 10 11
Arguments cons {_} _ _.
Arguments app {_} _ _.
Arguments Permutation {_} _ _.
12
Arguments Forall_cons {_} _ _ _ _ _.
Robbert Krebbers's avatar
Robbert Krebbers committed
13

14 15 16
Notation tail := tl.
Notation take := firstn.
Notation drop := skipn.
17

18 19 20
Arguments take {_} !_ !_ /.
Arguments drop {_} !_ !_ /.

Robbert Krebbers's avatar
Robbert Krebbers committed
21 22 23 24 25 26 27
Notation "(::)" := cons (only parsing) : C_scope.
Notation "( x ::)" := (cons x) (only parsing) : C_scope.
Notation "(:: l )" := (λ x, cons x l) (only parsing) : C_scope.
Notation "(++)" := app (only parsing) : C_scope.
Notation "( l ++)" := (app l) (only parsing) : C_scope.
Notation "(++ k )" := (λ l, app l k) (only parsing) : C_scope.

28 29 30 31 32 33 34 35 36
Infix "≡ₚ" := Permutation (at level 70, no associativity) : C_scope.
Notation "(≡ₚ)" := Permutation (only parsing) : C_scope.
Notation "( x ≡ₚ)" := (Permutation x) (only parsing) : C_scope.
Notation "(≡ₚ x )" := (λ y, y ≡ₚ x) (only parsing) : C_scope.
Notation "(≢ₚ)" := (λ x y, ¬x ≡ₚ y) (only parsing) : C_scope.
Notation "x ≢ₚ y":= (¬x ≡ₚ y) (at level 70, no associativity) : C_scope.
Notation "( x ≢ₚ)" := (λ y, x ≢ₚ y) (only parsing) : C_scope.
Notation "(≢ₚ x )" := (λ y, y ≢ₚ x) (only parsing) : C_scope.

37 38 39
(** * Definitions *)
(** The operation [l !! i] gives the [i]th element of the list [l], or [None]
in case [i] is out of bounds. *)
Robbert Krebbers's avatar
Robbert Krebbers committed
40
Instance list_lookup {A} : Lookup nat A (list A) :=
41
  fix go i l {struct l} : option A := let _ : Lookup _ _ _ := @go in
42
  match l with
43
  | [] => None | x :: l => match i with 0 => Some x | S i => l !! i end
44
  end.
45 46 47

(** The operation [alter f i l] applies the function [f] to the [i]th element
of [l]. In case [i] is out of bounds, the list is returned unchanged. *)
48 49
Instance list_alter {A} : Alter nat A (list A) := λ f,
  fix go i l {struct l} :=
50 51
  match l with
  | [] => []
52
  | x :: l => match i with 0 => f x :: l | S i => x :: go i l end
53
  end.
54

55 56
(** The operation [<[i:=x]> l] overwrites the element at position [i] with the
value [x]. In case [i] is out of bounds, the list is returned unchanged. *)
57 58 59 60 61 62
Instance list_insert {A} : Insert nat A (list A) :=
  fix go i y l {struct l} := let _ : Insert _ _ _ := @go in
  match l with
  | [] => []
  | x :: l => match i with 0 => y :: l | S i => x :: <[i:=y]>l end
  end.
63

64 65 66
(** The operation [delete i l] removes the [i]th element of [l] and moves
all consecutive elements one position ahead. In case [i] is out of bounds,
the list is returned unchanged. *)
67 68
Instance list_delete {A} : Delete nat (list A) :=
  fix go (i : nat) (l : list A) {struct l} : list A :=
69 70
  match l with
  | [] => []
71
  | x :: l => match i with 0 => l | S i => x :: @delete _ _ go i l end
72
  end.
73 74 75

(** The function [option_list o] converts an element [Some x] into the
singleton list [[x]], and [None] into the empty list [[]]. *)
Robbert Krebbers's avatar
Robbert Krebbers committed
76
Definition option_list {A} : option A → list A := option_rect _ (λ x, [x]) [].
77 78
Definition list_singleton {A} (l : list A) : option A :=
  match l with [x] => Some x | _ => None end.
Robbert Krebbers's avatar
Robbert Krebbers committed
79 80 81 82

(** The function [filter P l] returns the list of elements of [l] that
satisfies [P]. The order remains unchanged. *)
Instance list_filter {A} : Filter A (list A) :=
83
  fix go P _ l := let _ : Filter _ _ := @go in
Robbert Krebbers's avatar
Robbert Krebbers committed
84 85
  match l with
  | [] => []
86
  | x :: l => if decide (P x) then x :: filter P l else filter P l
87 88 89 90
  end.

(** The function [list_find P l] returns the first index [i] whose element
satisfies the predicate [P]. *)
91
Definition list_find {A} P `{∀ x, Decision (P x)} : list A → option (nat * A) :=
92 93
  fix go l :=
  match l with
94 95
  | [] => None
  | x :: l => if decide (P x) then Some (0,x) else prod_map S id <$> go l
96
  end.
Robbert Krebbers's avatar
Robbert Krebbers committed
97 98 99 100

(** The function [replicate n x] generates a list with length [n] of elements
with value [x]. *)
Fixpoint replicate {A} (n : nat) (x : A) : list A :=
101
  match n with 0 => [] | S n => x :: replicate n x end.
Robbert Krebbers's avatar
Robbert Krebbers committed
102 103 104 105

(** The function [reverse l] returns the elements of [l] in reverse order. *)
Definition reverse {A} (l : list A) : list A := rev_append l [].

106 107 108 109
(** The function [last l] returns the last element of the list [l], or [None]
if the list [l] is empty. *)
Fixpoint last {A} (l : list A) : option A :=
  match l with [] => None | [x] => Some x | _ :: l => last l end.
110

Robbert Krebbers's avatar
Robbert Krebbers committed
111 112 113 114 115 116
(** The function [resize n y l] takes the first [n] elements of [l] in case
[length l ≤ n], and otherwise appends elements with value [x] to [l] to obtain
a list of length [n]. *)
Fixpoint resize {A} (n : nat) (y : A) (l : list A) : list A :=
  match l with
  | [] => replicate n y
117
  | x :: l => match n with 0 => [] | S n => x :: resize n y l end
Robbert Krebbers's avatar
Robbert Krebbers committed
118 119 120
  end.
Arguments resize {_} !_ _ !_.

121 122 123
(** The function [reshape k l] transforms [l] into a list of lists whose sizes
are specified by [k]. In case [l] is too short, the resulting list will be
padded with empty lists. In case [l] is too long, it will be truncated. *)
124 125
Fixpoint reshape {A} (szs : list nat) (l : list A) : list (list A) :=
  match szs with
126
  | [] => [] | sz :: szs => take sz l :: reshape szs (drop sz l)
127 128
  end.

129
Definition sublist_lookup {A} (i n : nat) (l : list A) : option (list A) :=
130 131 132 133
  guard (i + n ≤ length l); Some (take n (drop i l)).
Definition sublist_alter {A} (f : list A → list A)
    (i n : nat) (l : list A) : list A :=
  take i l ++ f (take n (drop i l)) ++ drop (i + n) l.
134

135 136 137 138
(** Functions to fold over a list. We redefine [foldl] with the arguments in
the same order as in Haskell. *)
Notation foldr := fold_right.
Definition foldl {A B} (f : A → B → A) : A → list B → A :=
139
  fix go a l := match l with [] => a | x :: l => go (f a x) l end.
140 141 142

(** The monadic operations. *)
Instance list_ret: MRet list := λ A x, x :: @nil A.
143 144
Instance list_fmap : FMap list := λ A B f,
  fix go (l : list A) := match l with [] => [] | x :: l => f x :: go l end.
145 146 147 148 149 150
Instance list_omap : OMap list := λ A B f,
  fix go (l : list A) :=
  match l with
  | [] => []
  | x :: l => match f x with Some y => y :: go l | None => go l end
  end.
151 152
Instance list_bind : MBind list := λ A B f,
  fix go (l : list A) := match l with [] => [] | x :: l => f x ++ go l end.
153 154
Instance list_join: MJoin list :=
  fix go A (ls : list (list A)) : list A :=
155
  match ls with [] => [] | l :: ls => l ++ @mjoin _ go _ ls end.
156
Definition mapM `{MBind M, MRet M} {A B} (f : A → M B) : list A → M (list B) :=
157
  fix go l :=
158
  match l with [] => mret [] | x :: l => y ← f x; k ← go l; mret (y :: k) end.
159 160 161 162 163

(** We define stronger variants of map and fold that allow the mapped
function to use the index of the elements. *)
Definition imap_go {A B} (f : nat → A → B) : nat → list A → list B :=
  fix go (n : nat) (l : list A) :=
164
  match l with [] => [] | x :: l => f n x :: go (S n) l end.
165
Definition imap {A B} (f : nat → A → B) : list A → list B := imap_go f 0.
166 167 168 169 170 171 172 173 174 175 176
Definition zipped_map {A B} (f : list A → list A → A → B) :
  list A → list A → list B := fix go l k :=
  match k with [] => [] | x :: k => f l k x :: go (x :: l) k end.

Inductive zipped_Forall {A} (P : list A → list A → A → Prop) :
    list A → list A → Prop :=
  | zipped_Forall_nil l : zipped_Forall P l []
  | zipped_Forall_cons l k x :
     P l k x → zipped_Forall P (x :: l) k → zipped_Forall P l (x :: k).
Arguments zipped_Forall_nil {_ _} _.
Arguments zipped_Forall_cons {_ _} _ _ _ _ _.
177

178 179 180 181 182 183 184
(** The function [mask f βs l] applies the function [f] to elements in [l] at
positions that are [true] in [βs]. *)
Fixpoint mask {A} (f : A → A) (βs : list bool) (l : list A) : list A :=
  match βs, l with
  | β :: βs, x :: l => (if β then f x else x) :: mask f βs l
  | _, _ => l
  end.
185 186 187 188

(** The function [permutations l] yields all permutations of [l]. *)
Fixpoint interleave {A} (x : A) (l : list A) : list (list A) :=
  match l with
189
  | [] => [[x]]| y :: l => (x :: y :: l) :: ((y ::) <$> interleave x l)
190 191
  end.
Fixpoint permutations {A} (l : list A) : list (list A) :=
192
  match l with [] => [[]] | x :: l => permutations l ≫= interleave x end.
193

194 195
(** The predicate [suffix_of] holds if the first list is a suffix of the second.
The predicate [prefix_of] holds if the first list is a prefix of the second. *)
196 197
Definition suffix_of {A} : relation (list A) := λ l1 l2, ∃ k, l2 = k ++ l1.
Definition prefix_of {A} : relation (list A) := λ l1 l2, ∃ k, l2 = l1 ++ k.
198 199
Infix "`suffix_of`" := suffix_of (at level 70) : C_scope.
Infix "`prefix_of`" := prefix_of (at level 70) : C_scope.
200 201
Hint Extern 0 (?x `prefix_of` ?y) => reflexivity.
Hint Extern 0 (?x `suffix_of` ?y) => reflexivity.
Robbert Krebbers's avatar
Robbert Krebbers committed
202

203 204 205 206 207 208 209 210
Section prefix_suffix_ops.
  Context `{∀ x y : A, Decision (x = y)}.
  Definition max_prefix_of : list A → list A → list A * list A * list A :=
    fix go l1 l2 :=
    match l1, l2 with
    | [], l2 => ([], l2, [])
    | l1, [] => (l1, [], [])
    | x1 :: l1, x2 :: l2 =>
211
      if decide_rel (=) x1 x2
212
      then prod_map id (x1 ::) (go l1 l2) else (x1 :: l1, x2 :: l2, [])
213 214 215 216 217
    end.
  Definition max_suffix_of (l1 l2 : list A) : list A * list A * list A :=
    match max_prefix_of (reverse l1) (reverse l2) with
    | (k1, k2, k3) => (reverse k1, reverse k2, reverse k3)
    end.
218 219
  Definition strip_prefix (l1 l2 : list A) := (max_prefix_of l1 l2).1.2.
  Definition strip_suffix (l1 l2 : list A) := (max_suffix_of l1 l2).1.2.
220
End prefix_suffix_ops.
Robbert Krebbers's avatar
Robbert Krebbers committed
221

222
(** A list [l1] is a sublist of [l2] if [l2] is obtained by removing elements
223 224 225
from [l1] without changing the order. *)
Inductive sublist {A} : relation (list A) :=
  | sublist_nil : sublist [] []
226
  | sublist_skip x l1 l2 : sublist l1 l2 → sublist (x :: l1) (x :: l2)
227
  | sublist_cons x l1 l2 : sublist l1 l2 → sublist l1 (x :: l2).
228
Infix "`sublist`" := sublist (at level 70) : C_scope.
229
Hint Extern 0 (?x `sublist` ?y) => reflexivity.
230 231

(** A list [l2] contains a list [l1] if [l2] is obtained by removing elements
232
from [l1] while possiblity changing the order. *)
233 234 235 236
Inductive contains {A} : relation (list A) :=
  | contains_nil : contains [] []
  | contains_skip x l1 l2 : contains l1 l2 → contains (x :: l1) (x :: l2)
  | contains_swap x y l : contains (y :: x :: l) (x :: y :: l)
237
  | contains_cons x l1 l2 : contains l1 l2 → contains l1 (x :: l2)
238 239
  | contains_trans l1 l2 l3 : contains l1 l2 → contains l2 l3 → contains l1 l3.
Infix "`contains`" := contains (at level 70) : C_scope.
240
Hint Extern 0 (?x `contains` ?y) => reflexivity.
241 242 243 244 245 246 247 248 249 250

Section contains_dec_help.
  Context {A} {dec : ∀ x y : A, Decision (x = y)}.
  Fixpoint list_remove (x : A) (l : list A) : option (list A) :=
    match l with
    | [] => None
    | y :: l => if decide (x = y) then Some l else (y ::) <$> list_remove x l
    end.
  Fixpoint list_remove_list (k : list A) (l : list A) : option (list A) :=
    match k with
251
    | [] => Some l | x :: k => list_remove x l ≫= list_remove_list k
252 253
    end.
End contains_dec_help.
254

255 256 257 258 259
Inductive Forall3 {A B C} (P : A → B → C → Prop) :
     list A → list B → list C → Prop :=
  | Forall3_nil : Forall3 P [] [] []
  | Forall3_cons x y z l k k' :
     P x y z → Forall3 P l k k' → Forall3 P (x :: l) (y :: k) (z :: k').
260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284

(** Set operations on lists *)
Section list_set.
  Context {A} {dec : ∀ x y : A, Decision (x = y)}.
  Global Instance elem_of_list_dec {dec : ∀ x y : A, Decision (x = y)}
    (x : A) : ∀ l, Decision (x ∈ l).
  Proof.
   refine (
    fix go l :=
    match l return Decision (x ∈ l) with
    | [] => right _
    | y :: l => cast_if_or (decide (x = y)) (go l)
    end); clear go dec; subst; try (by constructor); abstract by inversion 1.
  Defined.
  Fixpoint remove_dups (l : list A) : list A :=
    match l with
    | [] => []
    | x :: l =>
      if decide_rel (∈) x l then remove_dups l else x :: remove_dups l
    end.
  Fixpoint list_difference (l k : list A) : list A :=
    match l with
    | [] => []
    | x :: l =>
      if decide_rel (∈) x k
285
      then list_difference l k else x :: list_difference l k
286
    end.
287
  Definition list_union (l k : list A) : list A := list_difference l k ++ k.
288 289 290 291 292
  Fixpoint list_intersection (l k : list A) : list A :=
    match l with
    | [] => []
    | x :: l =>
      if decide_rel (∈) x k
293
      then x :: list_intersection l k else list_intersection l k
294 295 296 297 298 299 300 301 302
    end.
  Definition list_intersection_with (f : A → A → option A) :
    list A → list A → list A := fix go l k :=
    match l with
    | [] => []
    | x :: l => foldr (λ y,
        match f x y with None => id | Some z => (z ::) end) (go l k) k
    end.
End list_set.
303 304

(** * Basic tactics on lists *)
305 306 307
(** The tactic [discriminate_list_equality] discharges a goal if it contains
a list equality involving [(::)] and [(++)] of two lists that have a different
length as one of its hypotheses. *)
308 309
Tactic Notation "discriminate_list_equality" hyp(H) :=
  apply (f_equal length) in H;
310
  repeat (csimpl in H || rewrite app_length in H); exfalso; lia.
311
Tactic Notation "discriminate_list_equality" :=
312 313 314
  match goal with
  | H : @eq (list _) _ _ |- _ => discriminate_list_equality H
  end.
315

316 317 318
(** The tactic [simplify_list_equality] simplifies hypotheses involving
equalities on lists using injectivity of [(::)] and [(++)]. Also, it simplifies
lookups in singleton lists. *)
319 320 321 322 323 324 325 326 327
Lemma app_injective_1 {A} (l1 k1 l2 k2 : list A) :
  length l1 = length k1 → l1 ++ l2 = k1 ++ k2 → l1 = k1 ∧ l2 = k2.
Proof. revert k1. induction l1; intros [|??]; naive_solver. Qed.
Lemma app_injective_2 {A} (l1 k1 l2 k2 : list A) :
  length l2 = length k2 → l1 ++ l2 = k1 ++ k2 → l1 = k1 ∧ l2 = k2.
Proof.
  intros ? Hl. apply app_injective_1; auto.
  apply (f_equal length) in Hl. rewrite !app_length in Hl. lia.
Qed.
328
Ltac simplify_list_equality :=
329
  repeat match goal with
330
  | _ => progress simplify_equality'
331
  | H : _ ++ _ = _ ++ _ |- _ => first
332 333 334
    [ apply app_inv_head in H | apply app_inv_tail in H
    | apply app_injective_1 in H; [destruct H|done]
    | apply app_injective_2 in H; [destruct H|done] ]
Robbert Krebbers's avatar
Robbert Krebbers committed
335
  | H : [?x] !! ?i = Some ?y |- _ =>
336
    destruct i; [change (Some x = Some y) in H | discriminate]
337
  end.
338

339 340
(** * General theorems *)
Section general_properties.
Robbert Krebbers's avatar
Robbert Krebbers committed
341
Context {A : Type}.
342 343
Implicit Types x y z : A.
Implicit Types l k : list A.
Robbert Krebbers's avatar
Robbert Krebbers committed
344

345 346 347
Global Instance: Injective2 (=) (=) (=) (@cons A).
Proof. by injection 1. Qed.
Global Instance: ∀ k, Injective (=) (=) (k ++).
348
Proof. intros ???. apply app_inv_head. Qed.
349
Global Instance: ∀ k, Injective (=) (=) (++ k).
350
Proof. intros ???. apply app_inv_tail. Qed.
351 352 353 354 355 356
Global Instance: Associative (=) (@app A).
Proof. intros ???. apply app_assoc. Qed.
Global Instance: LeftId (=) [] (@app A).
Proof. done. Qed.
Global Instance: RightId (=) [] (@app A).
Proof. intro. apply app_nil_r. Qed.
357

358
Lemma app_nil l1 l2 : l1 ++ l2 = [] ↔ l1 = [] ∧ l2 = [].
359
Proof. split. apply app_eq_nil. by intros [-> ->]. Qed.
360 361
Lemma app_singleton l1 l2 x :
  l1 ++ l2 = [x] ↔ l1 = [] ∧ l2 = [x] ∨ l1 = [x] ∧ l2 = [].
362
Proof. split. apply app_eq_unit. by intros [[-> ->]|[-> ->]]. Qed.
363 364 365
Lemma cons_middle x l1 l2 : l1 ++ x :: l2 = l1 ++ [x] ++ l2.
Proof. done. Qed.
Lemma list_eq l1 l2 : (∀ i, l1 !! i = l2 !! i) → l1 = l2.
366 367
Proof.
  revert l2. induction l1; intros [|??] H.
368
  * done.
369 370
  * discriminate (H 0).
  * discriminate (H 0).
371
  * f_equal; [by injection (H 0)|]. apply (IHl1 _ $ λ i, H (S i)).
372
Qed.
373
Global Instance list_eq_dec {dec : ∀ x y, Decision (x = y)} : ∀ l k,
374
  Decision (l = k) := list_eq_dec dec.
375 376 377 378 379 380 381 382
Global Instance list_eq_nil_dec l : Decision (l = []).
Proof. by refine match l with [] => left _ | _ => right _ end. Defined.
Lemma list_singleton_reflect l :
  option_reflect (λ x, l = [x]) (length l ≠ 1) (list_singleton l).
Proof. by destruct l as [|? []]; constructor. Defined.

Definition nil_length : length (@nil A) = 0 := eq_refl.
Definition cons_length x l : length (x :: l) = S (length l) := eq_refl.
383
Lemma nil_or_length_pos l : l = [] ∨ length l ≠ 0.
384
Proof. destruct l; simpl; auto with lia. Qed.
385
Lemma nil_length_inv l : length l = 0 → l = [].
386 387
Proof. by destruct l. Qed.
Lemma lookup_nil i : @nil A !! i = None.
388
Proof. by destruct i. Qed.
389
Lemma lookup_tail l i : tail l !! i = l !! S i.
390
Proof. by destruct l. Qed.
391 392
Lemma lookup_lt_Some l i x : l !! i = Some x → i < length l.
Proof.
393
  revert i. induction l; intros [|?] ?; simplify_equality'; auto with arith.
394 395 396 397 398
Qed.
Lemma lookup_lt_is_Some_1 l i : is_Some (l !! i) → i < length l.
Proof. intros [??]; eauto using lookup_lt_Some. Qed.
Lemma lookup_lt_is_Some_2 l i : i < length l → is_Some (l !! i).
Proof.
399
  revert i. induction l; intros [|?] ?; simplify_equality'; eauto with lia.
400 401 402 403 404 405 406 407 408
Qed.
Lemma lookup_lt_is_Some l i : is_Some (l !! i) ↔ i < length l.
Proof. split; auto using lookup_lt_is_Some_1, lookup_lt_is_Some_2. Qed.
Lemma lookup_ge_None l i : l !! i = None ↔ length l ≤ i.
Proof. rewrite eq_None_not_Some, lookup_lt_is_Some. lia. Qed.
Lemma lookup_ge_None_1 l i : l !! i = None → length l ≤ i.
Proof. by rewrite lookup_ge_None. Qed.
Lemma lookup_ge_None_2 l i : length l ≤ i → l !! i = None.
Proof. by rewrite lookup_ge_None. Qed.
409 410 411
Lemma list_eq_same_length l1 l2 n :
  length l2 = n → length l1 = n →
  (∀ i x y, i < n → l1 !! i = Some x → l2 !! i = Some y → x = y) → l1 = l2.
Robbert Krebbers's avatar
Robbert Krebbers committed
412
Proof.
413 414 415 416 417
  intros <- Hlen Hl; apply list_eq; intros i. destruct (l2 !! i) as [x|] eqn:Hx.
  * destruct (lookup_lt_is_Some_2 l1 i) as [y Hy].
    { rewrite Hlen; eauto using lookup_lt_Some. }
    rewrite Hy; f_equal; apply (Hl i); eauto using lookup_lt_Some.
  * by rewrite lookup_ge_None, Hlen, <-lookup_ge_None.
Robbert Krebbers's avatar
Robbert Krebbers committed
418
Qed.
419
Lemma lookup_app_l l1 l2 i : i < length l1 → (l1 ++ l2) !! i = l1 !! i.
420
Proof. revert i. induction l1; intros [|?]; simpl; auto with lia. Qed.
421 422
Lemma lookup_app_l_Some l1 l2 i x : l1 !! i = Some x → (l1 ++ l2) !! i = Some x.
Proof. intros. rewrite lookup_app_l; eauto using lookup_lt_Some. Qed.
423
Lemma lookup_app_r l1 l2 i :
424
  length l1 ≤ i → (l1 ++ l2) !! i = l2 !! (i - length l1).
425 426 427 428 429 430 431 432 433 434 435
Proof. revert i. induction l1; intros [|?]; simpl; auto with lia. Qed.
Lemma lookup_app_Some l1 l2 i x :
  (l1 ++ l2) !! i = Some x ↔
    l1 !! i = Some x ∨ length l1 ≤ i ∧ l2 !! (i - length l1) = Some x.
Proof.
  split.
  * revert i. induction l1 as [|y l1 IH]; intros [|i] ?;
      simplify_equality'; auto with lia.
    destruct (IH i) as [?|[??]]; auto with lia.
  * intros [?|[??]]; auto using lookup_app_l_Some. by rewrite lookup_app_r.
Qed.
436 437 438
Lemma list_lookup_middle l1 l2 x n :
  n = length l1 → (l1 ++ x :: l2) !! n = Some x.
Proof. intros ->. by induction l1. Qed.
439

440 441
Lemma list_insert_alter l i x : <[i:=x]>l = alter (λ _, x) i l.
Proof. by revert i; induction l; intros []; intros; f_equal'. Qed.
442
Lemma alter_length f l i : length (alter f i l) = length l.
443
Proof. revert i. by induction l; intros [|?]; f_equal'. Qed.
444
Lemma insert_length l i x : length (<[i:=x]>l) = length l.
445
Proof. revert i. by induction l; intros [|?]; f_equal'. Qed.
446
Lemma list_lookup_alter f l i : alter f i l !! i = f <$> l !! i.
447
Proof. revert i. induction l. done. intros [|i]. done. apply (IHl i). Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
448
Lemma list_lookup_alter_ne f l i j : i ≠ j → alter f i l !! j = l !! j.
449
Proof.
450
  revert i j. induction l; [done|]. intros [][] ?; csimpl; auto with congruence.
451
Qed.
452
Lemma list_lookup_insert l i x : i < length l → <[i:=x]>l !! i = Some x.
453 454
Proof. revert i. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
Lemma list_lookup_insert_ne l i j x : i ≠ j → <[i:=x]>l !! j = l !! j.
455
Proof.
456
  revert i j. induction l; [done|]. intros [] [] ?; simpl; auto with congruence.
457
Qed.
458 459
Lemma list_lookup_other l i x :
  length l ≠ 1 → l !! i = Some x → ∃ j y, j ≠ i ∧ l !! j = Some y.
Robbert Krebbers's avatar
Robbert Krebbers committed
460
Proof.
461
  intros. destruct i, l as [|x0 [|x1 l]]; simplify_equality'.
Robbert Krebbers's avatar
Robbert Krebbers committed
462 463 464
  * by exists 1 x1.
  * by exists 0 x0.
Qed.
465 466
Lemma alter_app_l f l1 l2 i :
  i < length l1 → alter f i (l1 ++ l2) = alter f i l1 ++ l2.
467
Proof. revert i. induction l1; intros [|?] ?; f_equal'; auto with lia. Qed.
468
Lemma alter_app_r f l1 l2 i :
469
  alter f (length l1 + i) (l1 ++ l2) = l1 ++ alter f i l2.
470
Proof. revert i. induction l1; intros [|?]; f_equal'; auto. Qed.
471 472
Lemma alter_app_r_alt f l1 l2 i :
  length l1 ≤ i → alter f i (l1 ++ l2) = l1 ++ alter f (i - length l1) l2.
473 474 475 476
Proof.
  intros. assert (i = length l1 + (i - length l1)) as Hi by lia.
  rewrite Hi at 1. by apply alter_app_r.
Qed.
477 478
Lemma list_alter_id f l i : (∀ x, f x = x) → alter f i l = l.
Proof. intros ?. revert i. induction l; intros [|?]; f_equal'; auto. Qed.
479 480 481
Lemma list_alter_ext f g l k i :
  (∀ x, l !! i = Some x → f x = g x) → l = k → alter f i l = alter g i k.
Proof. intros H ->. revert i H. induction k; intros [|?] ?; f_equal'; auto. Qed.
482 483
Lemma list_alter_compose f g l i :
  alter (f ∘ g) i l = alter f i (alter g i l).
484
Proof. revert i. induction l; intros [|?]; f_equal'; auto. Qed.
485 486
Lemma list_alter_commute f g l i j :
  i ≠ j → alter f i (alter g j l) = alter g j (alter f i l).
487
Proof. revert i j. induction l; intros [|?][|?] ?; f_equal'; auto with lia. Qed.
488 489
Lemma insert_app_l l1 l2 i x :
  i < length l1 → <[i:=x]>(l1 ++ l2) = <[i:=x]>l1 ++ l2.
490
Proof. revert i. induction l1; intros [|?] ?; f_equal'; auto with lia. Qed.
491
Lemma insert_app_r l1 l2 i x : <[length l1+i:=x]>(l1 ++ l2) = l1 ++ <[i:=x]>l2.
492
Proof. revert i. induction l1; intros [|?]; f_equal'; auto. Qed.
493 494
Lemma insert_app_r_alt l1 l2 i x :
  length l1 ≤ i → <[i:=x]>(l1 ++ l2) = l1 ++ <[i - length l1:=x]>l2.
495 496 497 498
Proof.
  intros. assert (i = length l1 + (i - length l1)) as Hi by lia.
  rewrite Hi at 1. by apply insert_app_r.
Qed.
499
Lemma delete_middle l1 l2 x : delete (length l1) (l1 ++ x :: l2) = l1 ++ l2.
500
Proof. induction l1; f_equal'; auto. Qed.
501

502
(** ** Properties of the [elem_of] predicate *)
503
Lemma not_elem_of_nil x : x ∉ [].
504
Proof. by inversion 1. Qed.
505
Lemma elem_of_nil x : x ∈ [] ↔ False.
506
Proof. intuition. by destruct (not_elem_of_nil x). Qed.
507
Lemma elem_of_nil_inv l : (∀ x, x ∉ l) → l = [].
508
Proof. destruct l. done. by edestruct 1; constructor. Qed.
509 510
Lemma elem_of_not_nil x l : x ∈ l → l ≠ [].
Proof. intros ? ->. by apply (elem_of_nil x). Qed.
511
Lemma elem_of_cons l x y : x ∈ y :: l ↔ x = y ∨ x ∈ l.
512
Proof. split; [inversion 1; subst|intros [->|?]]; constructor (done). Qed.
513
Lemma not_elem_of_cons l x y : x ∉ y :: l ↔ x ≠ y ∧ x ∉ l.
Robbert Krebbers's avatar
Robbert Krebbers committed
514
Proof. rewrite elem_of_cons. tauto. Qed.
515
Lemma elem_of_app l1 l2 x : x ∈ l1 ++ l2 ↔ x ∈ l1 ∨ x ∈ l2.
516
Proof.
517
  induction l1.
518
  * split; [by right|]. intros [Hx|]; [|done]. by destruct (elem_of_nil x).
519
  * simpl. rewrite !elem_of_cons, IHl1. tauto.
520
Qed.
521
Lemma not_elem_of_app l1 l2 x : x ∉ l1 ++ l2 ↔ x ∉ l1 ∧ x ∉ l2.
Robbert Krebbers's avatar
Robbert Krebbers committed
522
Proof. rewrite elem_of_app. tauto. Qed.
523
Lemma elem_of_list_singleton x y : x ∈ [y] ↔ x = y.
524
Proof. rewrite elem_of_cons, elem_of_nil. tauto. Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
525
Global Instance elem_of_list_permutation_proper x : Proper ((≡ₚ) ==> iff) (x ∈).
526
Proof. induction 1; rewrite ?elem_of_nil, ?elem_of_cons; intuition. Qed.
527
Lemma elem_of_list_split l x : x ∈ l → ∃ l1 l2, l = l1 ++ x :: l2.
528
Proof.
529 530
  induction 1 as [x l|x y l ? [l1 [l2 ->]]]; [by eexists [], l|].
  by exists (y :: l1) l2.
531
Qed.
532
Lemma elem_of_list_lookup_1 l x : x ∈ l → ∃ i, l !! i = Some x.
533
Proof.
534 535
  induction 1 as [|???? IH]; [by exists 0 |].
  destruct IH as [i ?]; auto. by exists (S i).
536
Qed.
537
Lemma elem_of_list_lookup_2 l i x : l !! i = Some x → x ∈ l.
538
Proof.
539
  revert i. induction l; intros [|i] ?; simplify_equality'; constructor; eauto.
540
Qed.
541 542
Lemma elem_of_list_lookup l x : x ∈ l ↔ ∃ i, l !! i = Some x.
Proof. firstorder eauto using elem_of_list_lookup_1, elem_of_list_lookup_2. Qed.
543 544 545 546 547 548 549 550 551
Lemma elem_of_list_omap {B} (f : A → option B) l (y : B) :
  y ∈ omap f l ↔ ∃ x, x ∈ l ∧ f x = Some y.
Proof.
  split.
  * induction l as [|x l]; csimpl; repeat case_match; inversion 1; subst;
      setoid_rewrite elem_of_cons; naive_solver.
  * intros (x&Hx&?). induction Hx; csimpl; repeat case_match;
      simplify_equality; auto; constructor (by auto).
Qed.
552

553
(** ** Properties of the [NoDup] predicate *)
554 555
Lemma NoDup_nil : NoDup (@nil A) ↔ True.
Proof. split; constructor. Qed.
556
Lemma NoDup_cons x l : NoDup (x :: l) ↔ x ∉ l ∧ NoDup l.
557
Proof. split. by inversion 1. intros [??]. by constructor. Qed.
558
Lemma NoDup_cons_11 x l : NoDup (x :: l) → x ∉ l.
559
Proof. rewrite NoDup_cons. by intros [??]. Qed.
560
Lemma NoDup_cons_12 x l : NoDup (x :: l) → NoDup l.
561
Proof. rewrite NoDup_cons. by intros [??]. Qed.
562
Lemma NoDup_singleton x : NoDup [x].
563
Proof. constructor. apply not_elem_of_nil. constructor. Qed.
564
Lemma NoDup_app l k : NoDup (l ++ k) ↔ NoDup l ∧ (∀ x, x ∈ l → x ∉ k) ∧ NoDup k.
Robbert Krebbers's avatar
Robbert Krebbers committed
565
Proof.
566
  induction l; simpl.
567
  * rewrite NoDup_nil. setoid_rewrite elem_of_nil. naive_solver.
568
  * rewrite !NoDup_cons.
Robbert Krebbers's avatar
Robbert Krebbers committed
569
    setoid_rewrite elem_of_cons. setoid_rewrite elem_of_app. naive_solver.
Robbert Krebbers's avatar
Robbert Krebbers committed
570
Qed.
571
Global Instance NoDup_proper: Proper ((≡ₚ) ==> iff) (@NoDup A).
572 573 574 575 576 577 578
Proof.
  induction 1 as [|x l k Hlk IH | |].
  * by rewrite !NoDup_nil.
  * by rewrite !NoDup_cons, IH, Hlk.
  * rewrite !NoDup_cons, !elem_of_cons. intuition.
  * intuition.
Qed.
579 580
Lemma NoDup_lookup l i j x :
  NoDup l → l !! i = Some x → l !! j = Some x → i = j.
581 582 583 584 585 586
Proof.
  intros Hl. revert i j. induction Hl as [|x' l Hx Hl IH].
  { intros; simplify_equality. }
  intros [|i] [|j] ??; simplify_equality'; eauto with f_equal;
    exfalso; eauto using elem_of_list_lookup_2.
Qed.
587 588
Lemma NoDup_alt l :
  NoDup l ↔ ∀ i j x, l !! i = Some x → l !! j = Some x → i = j.
589
Proof.
590 591 592 593 594
  split; eauto using NoDup_lookup.
  induction l as [|x l IH]; intros Hl; constructor.
  * rewrite elem_of_list_lookup. intros [i ?].
    by feed pose proof (Hl (S i) 0 x); auto.
  * apply IH. intros i j x' ??. by apply (injective S), (Hl (S i) (S j) x').
595
Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
596

597 598 599 600 601 602
Section no_dup_dec.
  Context `{!∀ x y, Decision (x = y)}.
  Global Instance NoDup_dec: ∀ l, Decision (NoDup l) :=
    fix NoDup_dec l :=
    match l return Decision (NoDup l) with
    | [] => left NoDup_nil_2
603
    | x :: l =>
604 605 606 607 608 609 610 611
      match decide_rel (∈) x l with
      | left Hin => right (λ H, NoDup_cons_11 _ _ H Hin)
      | right Hin =>
        match NoDup_dec l with
        | left H => left (NoDup_cons_2 _ _ Hin H)
        | right H => right (H ∘ NoDup_cons_12 _ _)
        end
      end
612
    end.
613
  Lemma elem_of_remove_dups l x : x ∈ remove_dups l ↔ x ∈ l.
614 615 616 617
  Proof.
    split; induction l; simpl; repeat case_decide;
      rewrite ?elem_of_cons; intuition (simplify_equality; auto).
  Qed.
618
  Lemma NoDup_remove_dups l : NoDup (remove_dups l).
619 620 621 622
  Proof.
    induction l; simpl; repeat case_decide; try constructor; auto.
    by rewrite elem_of_remove_dups.
  Qed.
623
End no_dup_dec.
624

625 626 627 628 629 630 631 632 633 634 635 636 637 638 639 640 641 642 643 644 645 646 647 648 649 650 651 652 653 654 655 656 657 658 659 660 661 662 663 664 665 666 667 668 669 670 671 672 673 674 675 676 677 678 679 680 681 682 683 684 685 686 687
(** ** Set operations on lists *)
Section list_set.
  Context {dec : ∀ x y, Decision (x = y)}.
  Lemma elem_of_list_difference l k x : x ∈ list_difference l k ↔ x ∈ l ∧ x ∉ k.
  Proof.
    split; induction l; simpl; try case_decide;
      rewrite ?elem_of_nil, ?elem_of_cons; intuition congruence.
  Qed.
  Lemma NoDup_list_difference l k : NoDup l → NoDup (list_difference l k).
  Proof.
    induction 1; simpl; try case_decide.
    * constructor.
    * done.
    * constructor. rewrite elem_of_list_difference; intuition. done.
  Qed.
  Lemma elem_of_list_union l k x : x ∈ list_union l k ↔ x ∈ l ∨ x ∈ k.
  Proof.
    unfold list_union. rewrite elem_of_app, elem_of_list_difference.
    intuition. case (decide (x ∈ k)); intuition.
  Qed.
  Lemma NoDup_list_union l k : NoDup l → NoDup k → NoDup (list_union l k).
  Proof.
    intros. apply NoDup_app. repeat split.
    * by apply NoDup_list_difference.
    * intro. rewrite elem_of_list_difference. intuition.
    * done.
  Qed.
  Lemma elem_of_list_intersection l k x :
    x ∈ list_intersection l k ↔ x ∈ l ∧ x ∈ k.
  Proof.
    split; induction l; simpl; repeat case_decide;
      rewrite ?elem_of_nil, ?elem_of_cons; intuition congruence.
  Qed.
  Lemma NoDup_list_intersection l k : NoDup l → NoDup (list_intersection l k).
  Proof.
    induction 1; simpl; try case_decide.
    * constructor.
    * constructor. rewrite elem_of_list_intersection; intuition. done.
    * done.
  Qed.
  Lemma elem_of_list_intersection_with f l k x :
    x ∈ list_intersection_with f l k ↔ ∃ x1 x2,
      x1 ∈ l ∧ x2 ∈ k ∧ f x1 x2 = Some x.
  Proof.
    split.
    * induction l as [|x1 l IH]; simpl; [by rewrite elem_of_nil|].
      intros Hx. setoid_rewrite elem_of_cons.
      cut ((∃ x2, x2 ∈ k ∧ f x1 x2 = Some x)
        ∨ x ∈ list_intersection_with f l k); [naive_solver|].
      clear IH. revert Hx. generalize (list_intersection_with f l k).
      induction k; simpl; [by auto|].
      case_match; setoid_rewrite elem_of_cons; naive_solver.
    * intros (x1&x2&Hx1&Hx2&Hx). induction Hx1 as [x1|x1 ? l ? IH]; simpl.
      + generalize (list_intersection_with f l k).
        induction Hx2; simpl; [by rewrite Hx; left |].
        case_match; simpl; try setoid_rewrite elem_of_cons; auto.
      + generalize (IH Hx). clear Hx IH Hx2.
        generalize (list_intersection_with f l k).
        induction k; simpl; intros; [done|].
        case_match; simpl; rewrite ?elem_of_cons; auto.
  Qed.
End list_set.

688
(** ** Properties of the [filter] function *)
689 690 691 692 693 694 695
Section filter.
  Context (P : A → Prop) `{∀ x, Decision (P x)}.
  Lemma elem_of_list_filter l x : x ∈ filter P l ↔ P x ∧ x ∈ l.
  Proof.
    unfold filter. induction l; simpl; repeat case_decide;
       rewrite ?elem_of_nil, ?elem_of_cons; naive_solver.
  Qed.
696
  Lemma NoDup_filter l : NoDup l → NoDup (filter P l).
697 698 699 700 701
  Proof.
    unfold filter. induction 1; simpl; repeat case_decide;
      rewrite ?NoDup_nil, ?NoDup_cons, ?elem_of_list_filter; tauto.
  Qed.
End filter.
Robbert Krebbers's avatar
Robbert Krebbers committed
702

703 704 705
(** ** Properties of the [find] function *)
Section find.
  Context (P : A → Prop) `{∀ x, Decision (P x)}.
706 707
  Lemma list_find_Some l i x :
    list_find P l = Some (i,x) → l !! i = Some x ∧ P x.
708
  Proof.
709 710 711
    revert i; induction l; intros [] ?;
      repeat (match goal with x : prod _ _ |- _ => destruct x end
              || simplify_option_equality); eauto.
712
  Qed.
713
  Lemma list_find_elem_of l x : x ∈ l → P x → is_Some (list_find P l).
714
  Proof.
715
    induction 1 as [|x y l ? IH]; intros; simplify_option_equality; eauto.
716
    by destruct IH as [[i x'] ->]; [|exists (S i, x')].
717 718 719
  Qed.
End find.

720
(** ** Properties of the [reverse] function *)
721 722
Lemma reverse_nil : reverse [] = @nil A.
Proof. done. Qed.
723
Lemma reverse_singleton x : reverse [x] = [x].
724
Proof. done. Qed.
725
Lemma reverse_cons l x : reverse (x :: l) = reverse l ++ [x].
726
Proof. unfold reverse. by rewrite <-!rev_alt. Qed.
727
Lemma reverse_snoc l x : reverse (l ++ [x]) = x :: reverse l.
728
Proof. unfold reverse. by rewrite <-!rev_alt, rev_unit. Qed.
729
Lemma reverse_app l1 l2 : reverse (l1 ++ l2) = reverse l2 ++ reverse l1.
730
Proof. unfold reverse. rewrite <-!rev_alt. apply rev_app_distr. Qed.
731
Lemma reverse_length l : length (reverse l) = length l.
732
Proof. unfold reverse. rewrite <-!rev_alt. apply rev_length. Qed.
733
Lemma reverse_involutive l : reverse (reverse l) = l.
734
Proof. unfold reverse. rewrite <-!rev_alt. apply rev_involutive. Qed.
735 736 737 738 739 740 741 742 743 744 745 746 747 748 749
Lemma elem_of_reverse_2 x l : x ∈ l → x ∈ reverse l.
Proof.
  induction 1; rewrite reverse_cons, elem_of_app,
    ?elem_of_list_singleton; intuition.
Qed.
Lemma elem_of_reverse x l : x ∈ reverse l ↔ x ∈ l.
Proof.
  split; auto using elem_of_reverse_2.
  intros. rewrite <-(reverse_involutive l). by apply elem_of_reverse_2.
Qed.
Global Instance: Injective (=) (=) (@reverse A).
Proof.
  intros l1 l2 Hl.
  by rewrite <-(reverse_involutive l1), <-(reverse_involutive l2), Hl.
Qed.
750 751 752 753 754 755 756 757
Lemma sum_list_with_app (f : A → nat) l k :
  sum_list_with f (l ++ k) = sum_list_with f l + sum_list_with f k.
Proof. induction l; simpl; lia. Qed.
Lemma sum_list_with_reverse (f : A → nat) l :
  sum_list_with f (reverse l) = sum_list_with f l.
Proof.
  induction l; simpl; rewrite ?reverse_cons, ?sum_list_with_app; simpl; lia.
Qed.
758

759 760 761
(** ** Properties of the [last] function *)
Lemma last_snoc x l : last (l ++ [x]) = Some x.
Proof. induction l as [|? []]; simpl; auto. Qed.
762 763 764 765
Lemma last_reverse l : last (reverse l) = head l.
Proof. by destruct l as [|x l]; rewrite ?reverse_cons, ?last_snoc. Qed.
Lemma head_reverse l : head (reverse l) = last l.
Proof. by rewrite <-last_reverse, reverse_involutive. Qed.
766

767 768 769 770 771 772 773
(** ** Properties of the [take] function *)
Definition take_drop i l : take i l ++ drop i l = l := firstn_skipn i l.
Lemma take_drop_middle l i x :
  l !! i = Some x → take i l ++ x :: drop (S i) l = l.
Proof.
  revert i x. induction l; intros [|?] ??; simplify_equality'; f_equal; auto.
Qed.
774
Lemma take_nil n : take n (@nil A) = [].
Robbert Krebbers's avatar
Robbert Krebbers committed
775
Proof. by destruct n. Qed.
776
Lemma take_app l k : take (length l) (l ++ k) = l.
777
Proof. induction l; f_equal'; auto. Qed.
778
Lemma take_app_alt l k n : n = length l → take n (l ++ k) = l.
779 780 781
Proof. intros ->. by apply take_app. Qed.
Lemma take_app3_alt l1 l2 l3 n : n = length l1 → take n ((l1 ++ l2) ++ l3) = l1.
Proof. intros ->. by rewrite <-(associative_L (++)), take_app. Qed.
782
Lemma take_app_le l k n : n ≤ length l → take n (l ++ k) = take n l.
783
Proof. revert n. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
784 785 786
Lemma take_plus_app l k n m :
  length l = n → take (n + m) (l ++ k) = l ++ take m k.
Proof. intros <-. induction l; f_equal'; auto. Qed.
787 788
Lemma take_app_ge l k n :
  length l ≤ n → take n (l ++ k) = l ++ take (n - length l) k.
789
Proof. revert n. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
790
Lemma take_ge l n : length l ≤ n → take n l = l.
791
Proof. revert n. induction l; intros [|?] ?; f_equal'; auto with lia. Qed.
792
Lemma take_take l n m : take n (take m l) = take (min n m) l.
793
Proof. revert n m. induction l; intros [|?] [|?]; f_equal'; auto. Qed.
794
Lemma take_idempotent l n : take n (take n l) = take n l.
Robbert Krebbers's avatar
Robbert Krebbers committed
795
Proof. by rewrite take_take, Min.min_idempotent. Qed.
796
Lemma take_length l n : length (take n l) = min n (length l).
797
Proof. revert n. induction l; intros [|?]; f_equal'; done. Qed.
798
Lemma take_length_le l n : n ≤ length l → length (take n l) = n.
Robbert Krebbers's avatar
Robbert Krebbers committed
799
Proof. rewrite take_length. apply Min.min_l. Qed.
800 801
Lemma take_length_ge l n : length l ≤ n → length (take n l) = length l.
Proof. rewrite take_length. apply Min.min_r. Qed.
802
Lemma take_drop_commute l n m : take n (drop m l) = drop m (take (m + n) l).
Robbert Krebbers's avatar
Robbert Krebbers committed
803
Proof.
804
  revert n m. induction l; intros [|?][|?]; simpl; auto using take_nil with lia.
Robbert Krebbers's avatar
Robbert Krebbers committed
805
Qed.
806 807
Lemma lookup_take l n i : i < n → take n l !! i = l !! i.
Proof. revert n i. induction l; intros [|n] [|i] ?; simpl; auto with lia. Qed.
808
Lemma lookup_take_ge l n i : n ≤ i → take n l !! i = None.
Robbert Krebbers's avatar
Robbert Krebbers committed
809
Proof. revert n i. induction l; intros [|?] [|?] ?; simpl; auto with lia. Qed.
810
Lemma take_alter f l n i : n ≤ i → take n (alter f i l) = take n l.
Robbert Krebbers's avatar
Robbert Krebbers committed
811 812 813 814 815
Proof.
  intros. apply list_eq. intros j. destruct (le_lt_dec n j).
  * by rewrite !lookup_take_ge.
  * by rewrite !lookup_take, !list_lookup_alter_ne by lia.
Qed.
816
Lemma take_insert l n i x : n ≤ i → take n (<[i:=x]>l) = take n l.
817 818 819 820 821
Proof.
  intros. apply list_eq. intros j. destruct (le_lt_dec n j).
  * by rewrite !lookup_take_ge.
  * by rewrite !lookup_take, !list_lookup_insert_ne by lia.
Qed.
Robbert Krebbers's avatar
Robbert Krebbers committed
822

823
(** ** Properties of the [drop] function *)
824 825
Lemma drop_0 l : drop 0 l = l.
Proof. done. Qed.
826
Lemma drop_nil n : drop n (@nil A) = [].
Robbert Krebbers's avatar
Robbert Krebbers committed
827
Proof. by destruct n. Qed.
828
Lemma drop_length l n : length (drop n l) = length l - n.
829
Proof. revert n. by induction l; intros [|i]; f_equal'. Qed.
830 831
Lemma drop_ge l n : length l ≤ n → drop n l = [].
Proof. revert n. induction l; intros [|??]; simpl in *; auto with lia. Qed.
832
Lemma drop_all l : drop (length l) l = [].
833
Proof. by apply drop_ge. Qed.
834 835
Lemma drop_drop l n1 n2 : drop n1 (drop n2 l) = drop (n2 + n1) l.
Proof. revert n2. induction l; intros [|?]; simpl; rewrite ?drop_nil; auto. Qed.
836 837 838 839 840 841 842
Lemma drop_app_le l k n :
  n ≤ length l → drop n (l ++ k) = drop n l ++ k.
Proof. revert n. induction l; intros [|?]; simpl; auto with lia. Qed.
Lemma drop_app l k : drop (length l) (l ++ k) = k.
Proof. by rewrite drop_app_le, drop_all. Qed.
Lemma drop_app_alt l k n : n = length l → drop n (l ++ k) = k.
Proof. intros ->. by apply drop_app. Qed.
843 844 845
Lemma drop_app3_alt l1 l2 l3 n :
  n = length l1 → drop n ((l1 ++ l2) ++ l3) = l2 ++ l3.
Proof. intros ->. by rewrite <-(associative_L (++)), drop_app. Qed.
846 847 848 849 850 851
Lemma drop_app_ge l k n :
  length l ≤ n → drop n (l ++ k) = drop (n - length l) k.
Proof.
  intros. rewrite <-(Nat.sub_add (length l) n) at 1 by done.
  by rewrite Nat.add_comm, <-drop_drop, drop_app.
Qed.
852 853 854
Lemma drop_plus_app l k n m :
  length l = n → drop (n + m) (l ++ k) = drop m k.
Proof. intros <-. by rewrite <-drop_drop, drop_app. Qed.
855
Lemma lookup_drop l n i : drop n l !! i = l !! (n + i).
Robbert Krebbers's avatar
Robbert Krebbers committed
856
Proof. revert n i. induction l; intros [|i] ?; simpl; auto. Qed.
857
Lemma drop_alter f l n i : i < n → drop n (alter f i l) = drop n l.
Robbert Krebbers's avatar
Robbert Krebbers committed
858 859 860 861
Proof.
  intros. apply list_eq. intros j.
  by rewrite !lookup_drop, !list_lookup_alter_ne by lia.
Qed.
862
Lemma drop_insert l n i x : i < n → drop n (<[i:=x]>l) = drop n l.
863 864 865 866
Proof.
  intros. apply list_eq. intros j.
  by rewrite !lookup_drop, !list_lookup_insert_ne by lia.
Qed.
867
Lemma delete_take_drop l i : delete i l = take i l ++ drop (S i) l.
868
Proof. revert i. induction l; intros [|?]; f_equal'; auto. Qed.
869 870 871 872 873 874 875
Lemma take_take_drop l n m : take n l ++ take m (drop n l) = take (n + m) l.
Proof. revert n m. induction l; intros [|?] [|?]; f_equal'; auto. Qed.
Lemma drop_take_drop l n m : n ≤ m → drop n (take m l) ++ drop m l = drop n l.
Proof.
  revert n m. induction l; intros [|?] [|?] ?;
    f_equal'; auto using take_drop with lia.
Qed.
876 877

(** ** Properties of the [replicate] function *)
878
Lemma replicate_length n x : length (replicate n x) = n.
879
Proof. induction n; simpl; auto. Qed.
880 881 882 883 884 885 886 887 888
Lemma lookup_replicate n x y i :
  replicate n x !! i = Some y ↔ y = x ∧ i < n.
Proof.
  split.
  * revert i. induction n; intros [|?]; naive_solver auto with lia.
  * intros [-> Hi]. revert i Hi.
    induction n; intros [|?]; naive_solver auto with lia.
Qed.
Lemma lookup_replicate_1 n x y i :
889
  replicate n x !! i = Some y → y = x ∧ i < n.
890 891 892
Proof. by rewrite lookup_replicate. Qed.
Lemma lookup_replicate_2 n x i : i < n → replicate n x !! i = Some x.
Proof. by rewrite lookup_replicate. Qed.
893 894 895
Lemma lookup_replicate_None n x i : n ≤ i ↔ replicate n x !! i = None.
Proof.
  rewrite eq_None_not_Some, Nat.le_ngt. split.
896 897
  * intros Hin [x' Hx']; destruct Hin. rewrite lookup_replicate in Hx'; tauto.
  * intros Hx ?. destruct Hx. exists x; auto using lookup_replicate_2.
898 899 900
Qed.
Lemma elem_of_replicate_inv x n y : x ∈ replicate n y → x = y.
Proof. induction n; simpl; rewrite ?elem_of_nil, ?elem_of_cons; intuition. Qed.
901
Lemma replicate_S n x : replicate (S n) x = x :: replicate  n x.
902
Proof. done. Qed.
903
Lemma replicate_plus n m x :
Robbert Krebbers's avatar
Robbert Krebbers committed
904
  replicate (n + m) x = replicate n x ++ replicate m x.
905
Proof. induction n; f_equal'; auto. Qed.
906
Lemma take_replicate n m x : take n (replicate m x) = replicate (min n m) x.
907
Proof. revert m. by induction n; intros [|?]; f_equal'. Qed.
908
Lemma take_replicate_plus n m x : take n (replicate (n + m) x) = replicate n x.
Robbert Krebbers's avatar
Robbert Krebbers committed
909
Proof. by rewrite take_replicate, min_l by lia. Qed.
910
Lemma drop_replicate n m x : drop n (replicate m x) = replicate (m - n) x.
911
Proof. revert m. by induction n; intros [|?]; f_equal'. Qed.
912
Lemma drop_replicate_plus n m x : drop n (replicate (n + m) x) = replicate m x.
Robbert Krebbers's avatar
Robbert Krebbers committed
913
Proof. rewrite drop_replicate. f_equal. lia. Qed.
914
Lemma replicate_as_elem_of x n l :
915
  replicate n x = l ↔ length l = n ∧ ∀ y, y ∈ l → y = x.
916
Proof.
917 918 919 920
  split; [intros <-; eauto using elem_of_replicate_inv, replicate_length|].
  intros [<- Hl]. symmetry. induction l as [|y l IH]; f_equal'.
  * apply Hl. by left.
  * apply IH. intros ??. apply Hl. by right.
921
Qed.
922
Lemma reverse_replicate n x : reverse (replicate n x) = replicate n x.
923
Proof.
924 925
  symmetry. apply replicate_as_elem_of.
  rewrite reverse_length, replicate_length. split; auto.
926
  intros y. rewrite elem_of_reverse. by apply elem_of_replicate_inv.
927
Qed.
928 929
Lemma replicate_false βs n : length βs = n → replicate n false =.>* βs.
Proof. intros <-. by induction βs; simpl; constructor. Qed.
930

931
(** ** Properties of the [resize] function *)
932
Lemma resize_spec l n x : resize n x l = take n l ++ replicate (n - length l) x.
933
Proof. revert n. induction l; intros [|?]; f_equal'; auto. Qed.
934
Lemma resize_0 l x : resize 0 x l = [].
Robbert Krebbers's avatar
Robbert Krebbers committed
935
Proof. by destruct l. Qed.
936
Lemma resize_nil n x : resize n x [] = replicate n x.
937
Proof. rewrite resize_spec. rewrite take_nil. f_equal'. lia. Qed.
938 939
Lemma resize_ge l n x :
  length l ≤ n → resize n x l = l ++ replicate (n - length l) x.
Robbert Krebbers's avatar
Robbert Krebbers committed
940
Proof. intros. by rewrite resize_spec, take_ge. Qed.
941
Lemma resize_le l n x : n ≤ length l → resize n x l = take n l.
Robbert Krebbers's avatar
Robbert Krebbers committed
942
Proof.
943
  intros. rewrite resize_spec, (proj2 (Nat.sub_0_le _ _)) by done.
944
  simpl. by rewrite (right_id_L [] (++)).
Robbert Krebbers's avatar
Robbert Krebbers committed
945
Qed.
946
Lemma resize_all l x : resize (length l) x l = l.
Robbert Krebbers's avatar
Robbert Krebbers committed
947
Proof. intros. by rewrite resize_le, take_ge. Qed.
948
Lemma resize_all_alt l n x : n = length l → resize n x l = l.
949
Proof. intros ->. by rewrite resize_all. Qed.
950
Lemma resize_plus l n m x :
Robbert Krebbers's avatar
Robbert Krebbers committed
951 952
  resize (n + m) x l = resize n x l ++ resize m x (drop n l).
Proof.
953
  revert n m. induction l; intros [|?] [|?]; f_equal'; auto.
954
  * by rewrite Nat.add_0_r, (right_id_L [] (++)).
Robbert Krebbers's avatar
Robbert Krebbers committed
955 956
  * by rewrite replicate_plus.
Qed.
957 958
Lemma resize_plus_eq l n m x :
  length l = n → resize (n + m) x l = l ++ replicate m x.
959
Proof. intros <-. by rewrite resize_plus, resize_all, drop_all, resize_nil. Qed.
960 961
Lemma resize_app_le l1 l2 n x :
  n ≤ length l1 → resize n x (l1 ++ l2) = resize n x l1.
Robbert Krebbers's avatar
Robbert Krebbers committed
962
Proof.
963
  intros. by rewrite !resize_le, take_app_le by (rewrite ?app_length; lia).
Robbert Krebbers's avatar
Robbert Krebbers committed
964
Qed.
965 966
Lemma resize_app l1 l2 n x : n = length l1 → resize n x (l1 ++ l2) = l1.
Proof. intros ->. by rewrite resize_app_le, resize_all. Qed.